2007
DOI: 10.1136/jcp.2007.050054
|View full text |Cite
|
Sign up to set email alerts
|

Chronic fatigue syndrome is associated with chronic enterovirus infection of the stomach

Abstract: Enterovirus VP1, RNA and non-cytopathic viruses were detected in the stomach biopsy specimens of CFS patients with chronic abdominal complaints. A significant subset of CFS patients may have a chronic, disseminated, non-cytolytic form of enteroviral infection, which could be diagnosed by stomach biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 33 publications
(27 reference statements)
3
79
1
7
Order By: Relevance
“…Several investigators have reported enteroviral involvement in some cases of CFS. [169][170][171][172][173][174][175][176] The most provocative recent report involved 165 consecutive patients with CFS accompanied by prominent gastrointestinal symptoms. Each of them had biopsies of the gastric antrum, as did 34 control volunteers without CFS.…”
Section: Enteroviral Infectionmentioning
confidence: 99%
“…Several investigators have reported enteroviral involvement in some cases of CFS. [169][170][171][172][173][174][175][176] The most provocative recent report involved 165 consecutive patients with CFS accompanied by prominent gastrointestinal symptoms. Each of them had biopsies of the gastric antrum, as did 34 control volunteers without CFS.…”
Section: Enteroviral Infectionmentioning
confidence: 99%
“…One such antibody (clone 5D8/1) is marketed commercially by Dako. The antibody is monoclonal in origin, was raised against the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 VP1 protein of Coxsackievirus B5 and has provided particularly sensitive and specific detection opportunities such that it has now been used extensively to detect enterovirus in formalin fixed tissues [49][50][51][52][53][54][55]. In combination, therefore, the use of HIER and the availability of new antisera have enabled an increase in both the spectrum of enteroviral serotypes which can be detected in fixed tissues and an improvement in the sensitivity of their detection [49][50][51][52][53][54][55][56][57] (and unpublished results…”
Section: Increasing the Sensitivity Of Detection Of Viral Proteins Inmentioning
confidence: 99%
“…Except in the cases of transplant-recipients, respiratory or stool specimens were rarely positive in our hospitalized adult patients with suspected acute enteroviral infections, even in cases proven by sero-conversion. Similar to chronic enterovirus infection of the stomach [7], the diagnosis of chronic lung infection may be difficult without special staining for viral protein or cultures of lung tissues. The sensitivity of transbronchial biopsies is likely inferior to open lung biopsy due to smaller sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The lung tissue was cultured in WI-38 embryonic lung fibroblasts and enterovirus RNA was quantitated after 72 hours of incubation, as described [7]. Positive RNA samples were amplified with non-biotinylated primers and cloned into P-drive vector as described [6], and sequenced by Retrogen [San Diego, Ca].…”
Section: Introductionmentioning
confidence: 99%